Experimental Study on the Seismic Behavior of a Steel-Concrete Hybrid Structure with Buckling Restrained Braces - Liang Li; Guoqiang Li; Tianhua Zhou (Advances in Civil Engineering)
The damage to a concrete wall caused by a strong earthquake is generally concentrated at the bottom of the concrete wall, which seriously threatens the safety of the steel-concrete hybrid structure and is very difficult to repair after an earthquake. In this paper, a steel-concrete hybrid structure with buckling restrained braces at a scale of 1/10 is constructed and tested on a shaking table. First, the mechanical properties of the BRBs are obtained through a static reciprocating loading test. Then, the dynamic properties and seismic response of the steel-concrete hybrid structure with BRBs are obtained through shaking table tests. The results show that (1) the energy dissipation capacity of the BRBs is very good, and none of the BRBs buckle during the shaking table tests; (2) the steel beams and columns are basically in an elastic state; (3) all the cracks on the concrete wall are microcracks, which are widely distributed in floors 1–8 of the concrete walls; (4) the maximum interstory drift angle reaches 1/40, which indicates that the ductility of the steel-concrete hybrid structure is very good. In conclusion, BRBs can significantly improve the seismic performance of the steel-concrete hybrid structures.